Reduced Intracellular c-di-GMP Content Increases Expression of Quorum Sensing-Regulated Genes in Pseudomonas aeruginosa - Lin Chua, Song; Liu, Yang; Li, Yingying; Jun Ting, Hui; Kohli, Gurjeet S.; Cai, Zhao; Suwanchaikasem, Pipob; Kau Kit Goh, Kelvin; Pin Ng, Sean; Tolker-Nielsen, Tim; Yang, Liang; Givskov, Michael (Frontiers in Cellular and Infection Microbiology, 2017)
Cyclic-di-GMP (c-di-GMP) is an intracellular secondary messenger which controls the biofilm life cycle in many bacterial species. High intracellular c-di-GMP content enhances biofilm formation via the reduction of motility and production of biofilm matrix, while low c-di-GMP content in biofilm cells leads to increased motility and biofilm dispersal. While the effect of high c-di-GMP levels on bacterial lifestyles is well studied, the physiology of cells at low c-di-GMP levels remains unclear. Here, we showed that Pseudomonas aeruginosa cells with high and low intracellular c-di-GMP contents possessed distinct transcriptome profiles. There were 535 genes being upregulated and 432 genes downregulated in cells with low c-di-GMP, as compared to cells with high c-di-GMP. Interestingly, both rhl and pqs quorum-sensing (QS) operons were expressed at higher levels in cells with low intracellular c-di-GMP content compared with cells with higher c-di-GMP content. The induced expression of pqs and rhl QS required a functional PqsR, the transcriptional regulator of pqs QS. Next, we observed increased production of pqs and rhl-regulated virulence factors, such as pyocyanin and rhamnolipids, in P. aeruginosa cells with low c-di-GMP levels, conferring them with increased intracellular survival rates and cytotoxicity against murine macrophages. Hence, our data suggested that low intracellular c-di-GMP levels in bacteria could induce QS-regulated virulence, in particular rhamnolipids that cripple the cellular components of the innate immune system.